Thermodynamic Parameters for Solvation of Nano ZNO and Its Dopes In 50% DMSO - 50% DMF (V/V) Solutions at Different Temperatures - Gomaa, E. A; Kairy, M; Fekri, A; Sherif, Y.A (Asian Journal of Energy Transformation and Conservation, 2014)
The molal solubility for nano zinc oxide (ZnO) , copper (2%) doped ZnO , Fe(2%) doped ZnO , Ti(2%) doped ZnO , Ag (25) doped ZnO in 50%DMF and 50% DMSO, (v/v), volume to volume were measured at 293.15, 303.15 , 313.15, 323.15K . The thermodynamic parameters, Gibbs free energy of solvation, enthalpies and entropies of solvation were evaluated for nano zinc oxide and nano zinc oxide doped from the solubility measurements. These thermodynamic parameters explain the effect of doping elements on the thermodynamic behviours of nano zinc oxide in solvation process.